Local anaesthetic potential, metabolic profiling, molecular docking and in silico ADME studies of Ocimum forskolei, family Lamiaceae. Issue 22 (18th November 2021) - Zahran, Eman Maher; Abdelmohsen, Usama Ramadan; Shalash, Mahmoud. M.; Salem, M. Alaraby; Khalil, Hany Ezzat; Desoukey, Samar Yehia; Fouad, Mostafa Ahmed; Krischke, Markus; Mueller, Martin; Kamel, Mohamed Salah
Abstract: The present study aimed to detect the bioactive metabolites from Ocimum forskolei aerial parts which are responsible for the local anaesthetic activity of the ethyl acetate fraction. Following a bioassay-guided fractionation, twelve compounds were dereplicated from the ethyl acetate fraction which was the most potent one with a mean onset of action (1.43 ± 0.07****) min compared to tetracaine as a positive control (1.37 ± 0.07****) min. These compounds, along with seven other compounds (isolated by diverse chromatographic techniques) were subjected to a molecular docking study to declare the top scoring compounds predicted to be responsible for such activity. The results highlighted Rabdosiin and Apigenin-7-O-rutinoside as the main bioactive leaders of the local anaesthesia via forming multiple H- bonding with the sodium ion channels leading to their blockade and loss of pain sensation, which strongly supports the use of O. forskolei as a local anaesthetic agent. Graphical Abstract: